Effects of temperature and reaction time on yield and properties of biocrude produced by hydrothermal liquefaction of spirulina platensis - Villaver, Weene S.; De Leon, Rizalinda L.; Yap, Kristian July R. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Hydrothermal liquefaction (HTL) is a process technology suited for converting wet biomass like microalgae into biocrude oil. This study aims to investigate the effects of temperature and reaction time on the mass yield and the properties of HTL biocrude such as higher heating value (HHV) and composition. Moreover, it aims to examine the nitrogen content of the produced biocrude. Spirulina platensis, microalgae species , is used as feedback. Slurry of Spirulina prepared at 30% dry weight is processed in 5-mL mini-reactors. The reactors are heated at 280ºC, 320ºC, and 350ºC using a temperature controlled sandbath. Reaction times are varied at 15mins, 30mins, and 45 mins. Biocrude is produced and separated using dichloromethane (DCM) as solvent. The yield of biocrude varies with temperature and reaction time ranging from 25% to 40% by mass. Higher mass yield of biocrude is observed at lower temperature settings. HHV of biocrude is high at longer reaction time. Energy yield is high at the condition of high mass yield. Nitrogen content in biocrude is reduced and is lowest at high temperature and longer reaction time.
Thesis (M.S. Energy Engineering)--University of the Philippines Diliman
Keywords: Algal biofuels; Spirulina